Evolución de la política educativa francesa: de la igualdad a la diversidad. - Gavari Starkie, Elisa (Revista Complutense de Educación, 2006)
This article provides a brief summary and a revision of the evolution of the idea of equality and its implementation in the French educational policy since the birth of the modern State until now-a-days. The starting point is the origin of the national educational system of a liberal nature characterised by the duality of the structures which were maintained until the mid of the XXth Century. After the approval of the 1958 Constitution the first educational reforms were introduced in order to implement the principle of equal of opportunities. This article emphasises the strategy of diversification of the structures and the recognition of the importance of the vocation element of learning as strategies that come along with the principle of equal of opportunities and the provision of a common learning. Finally the article refers to the fact that at the end of the XXth century the principle of diversity has become the motor of the French education policy.